FRI0216 Long-Term Safety and Efficacy of Mavrilimumab, A Fully Human Granulocyte-Macrophage Colony-Stimulating Factor Receptor-Alpha Monoclonal Antibody, in Patients with Rheumatoid Arthritis. (15th July 2016) - Burmester, G.; McInnes, I.; Kremer, J.; Miranda, P.; Vencovský, J.; Godwood, A.; Albulescu, M.; Close, D.; Weinblatt, M.
Abstract : Background: Mavrilimumab, a fully human monoclonal antibody, which targets granulocyte-macrophage colony-stimulating factor receptor-α, has demonstrated efficacy and an acceptable safety profile in prior 12- and 24-week studies. 1, 2 Objectives: This analysis evaluated all long-term (LT) safety and efficacy, through 74 weeks of treatment, of mavrilimumab. Methods: This open-label extension (OLE) study (NCT01712399 ) enrolled adult rheumatoid arthritis (RA) patients (pts) who had completed the EARTH EXPLORER 1 2 and 2 (NCT01715896 ) Phase IIb studies or were rescued as inadequate responders (from Week 12). Pts received subcutaneous mavrilimumab 100 mg every other week (eow), consistent with data from the Phase IIa study 1 . The primary objective was to assess the LT risk:benefit ratio of mavrilimumab via evaluation of i) Treatment emergent adverse events (TEAEs), TE serious AEs (TESAEs), and independently adjudicated pulmonary function tests (PFTs) ii) Exploratory LT efficacy endpoints (DAS28–CRP/ACR responses). AEs with onset date after start of mavrilimumab are presented. Change from baseline (BL) in modified Total Sharp Score (mTSS) was used to explore radiographic progression in EARTH EXPLORER 1 pts. Results: At the 74 week (includes original study) cutoff, 391 pts had been enrolled in the OLE study. Of these, 329 (84.1%) continued on treatment, 62 (15.9%) discontinued (due to withdrawal of consent, 9 [2.3%]; adverse event, 7 [1.8%]; non study-related site closure, 20 [5.1%]; other, 24 [6.1%]; lost-to-follow-up, 1 [0.3%]; death [sudden cardiac arrest, preferred term cardiopulmonary failure], 1 [0.3%]), and 239 (61.1%) were assessed for efficacy at Week 74. Between the Phase IIb and OLE studies, 440 pts received mavrilimumab, with a safety exposure of 603 pt years (yr) and median duration of 1.6 yr. Most common TEAEs (n [/100 pt yr]) were nasopharyngitis (51 [8.45]), bronchitis (36 [5.97]) and hypertension (32 [5.30]); the serious infection rate was 1.82/100 pt yr. Pulmonary events/defined PFT changes occurred in a few pts and were generally transient with no signal identified (Table). Mavrilimumab demonstrated sustained efficacy (DAS28–CRP/ACR responses) (Table). After 74 weeks of treatment, 68% of pts showed no radiographic progression (<0.5 change in mTSS vs. BL) (Table ). Conclusions: Mavrilimumab continues to demonstrate a sustained efficacy and safety profile in pts with active RA, over the 74 week treatment duration reported. Although mavrilimumab 100 mg eow is suboptimal compared with 150 mg eow in DMARD-IR pts, 2 efficacy results are comparable with those of previous studies. 1, 2 References: Burmester G, et al. Ann Rheum Dis 2013;72:1445–1452 Burmester G, et al. Arthritis Rheum 2014;66:S1231 Acknowledgement: Funded by MedImmune. Editorial assistance: K Alexander, QXV Comms, an Ashfield business, UK Joint senior authors: D. Close and M. Weinblatt Disclosure of Interest: G. Burmester Consultant for: MedImmune, I. McInnes Grant/research support from: Research award to University of Glasgow, Consultant for: MedImmune, AstraZeneca, J. Kremer Shareholder of: Corrona, Grant/research support from: Abbvie, Amgen, Genentech, Lilly, Pfizer, Consultant for: Abbvie, Amgen, BMS, Genentech, Lilly, Pfizer, Employee of: Corrona, P. Miranda Grant/research support from: Clinical trials Amgen, Medimmune, Janssen, Pfizer, Celltrion, Abbott, Sanofi, Actelion, Merck & Co, Boehringer, BMS, Consultant for: Pfizer for Etanecept (fee less than USD5000), J. Vencovský Consultant for: Pfizer, Servier, Samsumg, Eli lilley, BMS, Novartis, A. Godwood Shareholder of: AstraZeneca, Employee of: MedImmune, M. Albulescu Employee of: MedImmune, D. Close, Employee of: MedImmune, M. Weinblatt, Grant/research support from: BMS, UCB, Crescendo Bioscience, Consultant for: MedImmune, AstraZeneca, Amgen, Abbvie, BMS, Crescendo Bioscience, Lilly, Pfizer, UCB, Roche